Treating Hyperglycemia From Eryngium caeruleum M. Bieb: In-vitro α-Glucosidase, Antioxidant, in-vivo Antidiabetic and Molecular Docking-Based Approaches - Sadiq, Abdul; Rashid, Umer; Ahmad, Sadiq; Zahoor, Mohammad; AlAjmi, Mohamed F.; Ullah, Riaz; Noman, Omar M.; Ullah, Farhat; Ayaz, Muhammad; Khan, Iftikhar; Islam, Zia-Ul; Ali, Waqar (Frontiers in Chemistry, 2020)
Natural-based drugs are believed to be safe, effective and economical. Based on the medicinal importance of the genus Eryngium and unexplored nature of Eryngium caeruleum, we have evaluated its antidiabetic and antioxidant potentials. Both in-vitro and in-vivo assays have been carried out for antidiabetic assays. The antioxidant activity was determined by using different free radicals [i.e., 1,1-diphenyl,2-picrylhydrazyl (DPPH), 2,2-azinobis[3-ethylbenzthiazoline]-6-sulfonic acid (ABTS), and hydrogen peroxide (H2O2)]. Moreover, different phytoconstituents were identified in the most active solvent fraction by GC-MS analysis. Furthermore, comparative fingerprints of methanolic extract and chloroform fraction were also analyzed via High Performance Liquid Chromatography coupled with Diode Array Detector (HPLC-DAD). The crude methanolic extract of E. caeruleum (Ec.Cr) and its sub-fractions [i.e., n-hexane (Ec.Hex), chloroform (Ec.Chf), ethyl acetate (Ec.EtAc), and aqueous (Ec.Aq) were employed in this study]. In the α-glucosidase inhibition assay, a concentration-dependent inhibitory response was observed against the enzyme. The most active sample was Ec.Chf which revealed an IC50 of 437 μg/ml in comparison to the standard acarbose (IC50 25 μg/ml). The rest of the samples showed moderate inhibition of α-glucosidase. In antioxidant assays, Ec.Chf and Ec.Cr exhibited a considerable scavenging effect against all the free radicals. The IC50 values recorded for Ec.Chf were 112, 109, and 150 μg/ml against DPPH, ABTS, and H2O2 respectively. Based on the in-vitro potential of Ec.Chf, this was subjected to the in-vivo model experiment. The Ec.Chf lowered the blood glucose level up to 10.3 mmol/L at 500 μg/Kg. The Ec.Chf was also subjected to GC-MS analysis. The GC-MS analysis confirmed the presence of 60 compounds. The identified phytoconstituents consist of some essential compounds previously reported with antidiabetic and antioxidant studies, which include thymol, tocopherol, phytol, nerolidol, (I)-neophytadiene, linolenic acid, and falcarinol. Similarly, the HPLC-DAD chromatograms of Ec.Cr and Ec.Chf exhibited a variety of peaks, which further demonstrates the possibility of important phytochemicals. In a nutshell, we can conclude that Eryngium caeruleum is a potential source of bioactive compounds which may be beneficial for the management of ailments like diabetes and free radicals mediated disorders. Molecular docking was performed to explore the possible role of all the identified bioactive compounds in the chloroform fraction of Eryngium caeruleum into active sites of the homology model of α-glucosidase.